The roll of the psychologist in the Tourette syndrome - Montezuma-del-Castillo, Oriele (2003)
The intention of this article is to present the different areas of psychologist performance for dealing with Tourette Syndrome. The syndrome is described in its varying degrees and its relationship with other generally associated disorders. Statistical data of 21 people with Tourette Syndrome, confronted with other international studies that considered these variables. Some characteristics and important considerations described in the treatment are: a) the individuality of the person with TS; b) groups; c)family; d) educative and/or socio labor environment.